Investigation of the Parameters of Marital Kinship (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This work compares and describes terminology related to marriage kinship in English and Uzbek. The terms used to describe marital kinship in society are essentially based on marriage, created by the marriage system. Socially, married couples, their parents, and their siblings on both sides are identified by the terms of marital kinship.